2020
DOI: 10.1364/ol.401738
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon polymerization with diode lasers emitting ultrashort pulses with high repetition rate

Abstract: In this Letter, we investigate the resolution of two-photon polymerization (2PP) with an amplified mode-locked external cavity diode laser with adjustable pulse length and a high repetition rate. The experimental results are analyzed with a newly developed 2PP model. Even with low pulse peak intensity, the produced structural dimensions are comparable to those generated by traditional 2PP laser sources. Thus, we show that a compact monolithic picosecond laser diode without amplification and with a repetition r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Tissue engineering is an interdisciplinary research field that applies materials and biological sciences to create artificial organs and tissue matrices [13]. Micro-/nanostructured biomaterials with specific characteristics and functions are in great demand in biomedical applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue engineering is an interdisciplinary research field that applies materials and biological sciences to create artificial organs and tissue matrices [13]. Micro-/nanostructured biomaterials with specific characteristics and functions are in great demand in biomedical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, numerous studies have been devoted to the manufacture of the surface pattern of biomaterials for exploring the role of contact guidance. In recent years, two-photon polymerization nanolithography micro/nanomanufacturing technology has become a powerful and useful manufacturing tool, which can generate two-dimensional (2D) to threedimensional (3D) arbitrary micro/nanotopologies of various materials with high spatial resolution, thus arousing great interest in cell and tissue engineering [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has already been demonstrated that monolithically mode-locked diode lasers are in principle suitable for 2PP, as shown in Ref. 19. However, ten individual scans at a speed of 10 µm/s were required to polymerize a single line.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid 2‚» photon absorption to cure SU8 photoresist without a post‚bake was investigated in 21 , where 1700 nm fs‚pulses were used and conclude that in their setup thermal curing of the material had larger impact than MPP. In 2020 Zyla et al used a compact monolithic picosecond (ps‚)laser diode and have achieved structural dimensions comparable to those generated by traditional MPP laser sources 22 . Wegener's group reported two‚step absorption instead of MPP in 2021 23 where a real electron (defect) state instead of a virtual was used for excitation.…”
Section: Introductionmentioning
confidence: 99%